PENGGUNAAN MINYAK Melaleuca bracteata DAN SARI BUAH JAMBU BIJI (Psidium guajava L.) SEBAGAI ATRAKTAN UNTUK MENGENDALIKAN LALAT BUAH (Bactrocera spp.) CABAI DI KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Arfan Arfan; Ahmad Taufiq Arminudin (Jurnal Agroteknologi, 2011)
This research aim to study the effect of Melaleuca bracteata and Psidium guajava as attractant to controlling fruit fly (Bactrocera spp.) throught different application times at paper plantation in Sigi Sulawesi Tengah. It was done since March until July 2010 in Maku village, District of Dolo, Sigi regency, Sulawesi Selatan Province of Indonesia. Randomized Block Design with 2 (two) factor and treatment was used by concetration of M. bracteata oil on three levels and application time on three levels. Concentration of M. Bracteata oil on extract of P. guajava as first factor, there were M1 = 0,40 ml of M. bracteata oil / 100 ml of P. guajava extract, M2 = 0,50 ml of M. bracteata oil / 100 ml of P. guajava extract, dan M3 = 0,60 ml of M. bracteata oil / 100 ml of P. guajava extract. The application time as second factor, there ara were W1 = 7 days, W2 = 10 days, and W3 = 13 days. The results showed that population of fruit fly at paper plantation reduced by application of M. bracteata oil. Application of 0,60 ml of M. bracteata oil / 100 ml of P. guajava extract every 10 days indicated the best attractant of the fruit fly. Others results of this research was discussed.